PENYEBAB DAN DAMPAK PERNIKAHAN DINI DI WILAYAH KERJA PUSKESMAS KABUN KABUPATEN ROKAN HULU TAHUN 2019: to determine the causes and effects of early marriage in the Work Area Of The Kabun Health Center In Rokan Hulu Regency Years 2019 - Nur Asjeti; Elfindri Elfindri; Zainal Abidin; Jasrida Yunita; Sri Wardani (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2021)
Abstract Early marriage to adolescents will cause problems both in reproductive health, economics and domestic violence. The impact of marriage at a young age is more evident in adolescent girls than in adolescent boys. Data from the Office of the Ministry of Religion in Rokan Hulu Regency the number of premature marriages under the age of 20 years in Kabun District is 49 0 people (36.8%). The purpose of this study was to determine the causes and effects of early marriage in the Work Area Of ​​The Kabun Health Center In Rokan Hulu Regency, based on the causes and impacts. This type of research is mixed methods. Samples / key informants 46 respondents were taken in total sampling, informants supporting midwives 1 person, village head 6 people, religious leaders 6 people. Data were analyzed univariately and using source, method and data triangulation. Quantitative research results showed 18 respondents (39.1%) had junior high school education, 22 respondents lack knowledge (47.8%), economic parents 22 respondents lack (47.8%), premarital sex 27 respondents (58.7%). Not pregnant out of wedlock 37 respondents (80.4%). The results of qualitative research, the impact of early marriage there were 3 cases of bleeding, 7 cases of cesarean section and premature labor, 1 case of abortion. The average husband's work is a palm harvest worker with a monthly income of Rp 1.5 million to Rp 2.5 million and the income received is not enough for daily needs. The majority of women (wife) have never experienced domestic violence either physically or verbally. Suggestions for Kabun healt center to collaborates with cross-sectors such as BKKBN, PKK and community leaders to empower the community about early marriage and activate PIK KRR in schools to provide counseling about early marriage and as peer counselors. The Office of Religious Affairs can facilitate the formation of Legal Awareness Community Groups that are fostered by various sectoral parties such as the police, community leaders so that the community understands that domestic violence is a criminal act that can be snared by the law. Keywords : Early Marriage, Causes, Impact